Age‐associated adipose tissue inflammation promotes monocyte chemotaxis and enhances atherosclerosis. Issue 2 (23rd January 2023) - Song, Jianrui; Farris, Diana; Ariza, Paola; Moorjani, Smriti; Varghese, Mita; Blin, Muriel; Chen, Judy; Tyrrell, Daniel; Zhang, Min; Singer, Kanakadurga; Salmon, Morgan; Goldstein, Daniel R.
Abstract: Although aging enhances atherosclerosis, we do not know if this occurs via alterations in circulating immune cells, lipid metabolism, vasculature, or adipose tissue. Here, we examined whether aging exerts a direct pro‐atherogenic effect on adipose tissue in mice. After demonstrating that aging augmented the inflammatory profile of visceral but not subcutaneous adipose tissue, we transplanted visceral fat from young or aged mice onto the right carotid artery of Ldlr −/− recipients. Aged fat transplants not only increased atherosclerotic plaque size with increased macrophage numbers in the adjacent carotid artery, but also in distal vascular territories, indicating that aging of the adipose tissue enhances atherosclerosis via secreted factors. By depleting macrophages from the visceral fat, we identified that adipose tissue macrophages are major contributors of the secreted factors. To identify these inflammatory factors, we found that aged fat transplants secreted increased levels of the inflammatory mediators TNFα, CXCL2, and CCL2, which synergized to promote monocyte chemotaxis. Importantly, the combined blockade of these inflammatory mediators impeded the ability of aged fat transplants to enhance atherosclerosis. In conclusion, our study reveals that aging enhances atherosclerosis via increased inflammation of visceral fat. Our study suggests that future therapies targeting the visceral fat may reduce atherosclerosis disease burden in the expanding older population. Abstract : Aging increases visceral fat inflammation including the increase of adipose tissue macrophages (MΦ). The macrophages in aged visceral fat then secrete increased inflammatory mediators specifically TNFα, CCL2 and CXCL2, which consequently promote an atherogenic phenotype on circulating monocytes. The monocytes gain increased expression of inflammatory markers, chemokine receptors and migration related genes, which leads to enhanced migration of monocytes towards the artery wall to promote atherogenesis.